The genre of Q&A sessions of oral presentations delivered by students enrolled in english for workplace communication - Seliman, Salbiah; Ahmad Fuad, Noor Izzati (2010)
This study is to seek out the structure of the moves utilised by students in Q&A sessions of oral presentations and the differences between the moves utilized by FP and FPPSM students enrolled in English for Workplace Communication. The Q&A sessions of the oral presentations of 44 third year students enrolled in the preceding subject from the two faculties in UTM were observed. The Q&A sessions were recorded and then transcribed and analysed to work out the moves. It was found that there was a specific structure of moves utilised by students in Q&A sessions of oral presentations. Some differences were found between the moves in Q&A sessions of FP students and those of FPPSM students. The structure of the moves in Q&A sessions needs to be explained to the students so that they are aware of the appropriate moves to be utilised during the Q&A sessions.